Bone health education in individuals with spinal cord injury or disease—the Bare Bones Podcast Series: plan it, produce it, post it! - Craven, B. Catharine; Kaiser, Anita; Blencowe, Lindsie A.; Jervis-Rademeyer, Hope; Boag, Lynn; Murphy, Wendy; Miyatani, Masae (Frontiers in Rehabilitation Sciences, 2024)
IntroductionThe Consortium for Spinal Cord Medicine's inaugural Clinical Practice Guideline for Bone Health and Osteoporosis Management for Individuals with Spinal Cord Injury or Disease (CSCM-CPG) was published in 2022 for a clinician audience. The aim of this project was to develop a podcast series to ensure people with lived experience with Spinal Cord Injury or Disease (PLEX) understand the CSCM-CPG content and know how to act to reduce their fracture risk.MethodsThe “Bare Bones Podcast Series” consists of nine episodes; one related to each CSCM-CPG chapter. The podcast content and the questions asked in each podcast were co-developed by PLEX partners (PLEX-P) and the project team. Two PLEX-P acted as co-hosts for the series. The invited speaker(s) were CSCM-CPG expert panel members who participated in an informal dialogue with the hosts. Each podcast closes with a specific action a listener can do to advance their bone health. The related Educational Action Planning Tool (EAT) handouts contain text and infographic information specific to each podcast episode and include key concepts and a specific actionable take-home message. Local PLEX reviewers (PLEX-R) were invited to review podcast episodes and EATs and provide their feedback through focus group participation or one-on-one (1:1) interviews. The project team revised the podcast episodes and the EATs based on feedback from the PLEX-R prior to releasing them online.ResultsNine podcast episodes and related EATs were designed and created collaboratively with 3 PLEX-P, 22 PLEX-R, 11 CSCM-CPG expert panel members, and the project team. The episodes were titled: “Introduction to the Bare Bones of Bone Health”; “Fracture 101”; “Blood Tests—a Window into You”; “I See Your Skeleton”; “Vitamin D for all, Calcium for Some”; “Get Moving and Loading”; “Pills or Poisons & Atomic Habits”; “Snap and Crack”; and “Directions for Research”. The Bare Bones Podcast Series was shared through the project website.ConclusionsThe podcasts will aid PLEX and their family caregivers to advocate for ongoing bone health assessments and to promote an ongoing dialogue with care team members regarding how to prevent fractures and fracture-related morbidity and mortality.